1998
DOI: 10.1038/sj.bmt.1701242
|View full text |Cite
|
Sign up to set email alerts
|

First and second apheresis in patients with multiple myeloma: no differences in tumor load and hematopoietic stem cell yield

Abstract: Multiple myeloma (MM) is a B cell malignancy characterized by the accumulation of clonal plasma cells in the bone marrow (BM) secreting a monoclonal immunoglobulin. Due to the limited success of conventional chemotherapies in MM, intensified high-dose (HD) chemotherapy regimens followed by autologous hematopoietic stem cell transplantation are now widely used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 20 publications
(15 reference statements)
0
13
0
Order By: Relevance
“…7,12,22 However, other studies have found no variation in the kinetics of tumor cell and CD34 þ stem cell mobilization. 7,20,23,24 Studies investigating the effect of the mobilization regimen on tumor cell contamination of the apheresis product have also yielded conflicting results. In one study, mobilization with G-CSF alone resulted in tumor cell contamination in 25% patients, whereas chemomobilization resulted in tumor cell contamination in 51% patients.…”
Section: Discussionmentioning
confidence: 99%
“…7,12,22 However, other studies have found no variation in the kinetics of tumor cell and CD34 þ stem cell mobilization. 7,20,23,24 Studies investigating the effect of the mobilization regimen on tumor cell contamination of the apheresis product have also yielded conflicting results. In one study, mobilization with G-CSF alone resulted in tumor cell contamination in 25% patients, whereas chemomobilization resulted in tumor cell contamination in 51% patients.…”
Section: Discussionmentioning
confidence: 99%
“…18,[28][29][30] Representative samples were obtained from each SCC without manipulation. To estimate the percent of clonotypic cells, limiting-dilution PCR with patient-specific CDR1/CDR3 primers was performed 18,[28][29][30][31][32][33][34] with DNA from 2 Â 10 5 cells per SCC serially log-diluted (ie 10-fold) with buffy-coat DNA (limiting-dilution PCR). Specimens giving all negative results were assessed by RT-PCR, whereas specimens giving positive results underwent limiting-dilution PCR.…”
Section: Assessing Clonotypic Contaminationmentioning
confidence: 99%
“…That the PCR assay used is sensitive enough to detect one cell in the PCR tube independent of the number of surrounding normal cells had been demonstrated by means of dilution series of the U266 myeloma cells in 500 000 melanoma cells (data previously shown). 20 Hence, the lowest dilution level with a positive PCR signal denoted the proportion of malignant cells in the sample. To further validate the PCR assay used, plasmids carrying the CDR3 regions of the tumor clone of three patients were diluted in 10-fold steps in placental DNA (Clontech) to simulate tumor loads from 0.1 down to 0.0001%.…”
Section: Proportion Of Clonotypic Cellsmentioning
confidence: 99%